(3GdMeGjI GdLfGFjI ddHQGeL h GdHjGfGJ GdeYGdLI EdcJQhfjkqG (B: s (3OQGSI ebGQfI (B/ s - (3MeGe YHOGddWja YHOGdTGai Mfai eYhVs; (3eOMJ YHOdMdje QeVGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3JYO GdMeGjI GdLfGFjI ddHQGeL h GdHjGfGJ ef GdehVhYGJ GdgGeI deG JJeJY Hg GdHQGeL h GdHjGfGJ ef bjeI GbJUGOjI YGdjI(B: (3fXQkG ddJbOe GdJcfhdhLi GdgGFd h GdJWhQ GdSQjY dKhQI GdeYdheGJ h GdJi GUHMJ PGJ GgejI GLJeGYjI h GbJUGOjI h KbGajI h SjGSjI(B: (3dPG dG HO ef ehGcHI GdJbOe GdJcfhdhLi h VQhQI hLhO MeGjI LfGFjI deYGdLJgG ef GdLQGFe GdJi bO JWQC YdjgG fJjLI dYOe hLhO fU JTQjYi ai GdbGfhf GdJbdjOi(B: (3h VQhQI EUOGQ JTQjY eYdheGJi NGU HGdLQGFe GdeYdheGJjI dQOY GdLfGI h MJi dG jUHM gfGc aQGZ JTQjYi HTCf gPg GdLQGFe GdeSJMOKI(B: (3h dVeGf SjQ GdJbOe GdJcfhdhLi Ohf YbHGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2017s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B379-412s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGNJQGb GdGdcJQhfjs; (3GdMeGjIs; (3GdeYdheGJs; (3GdfXe GdeYdheGJjIs; (3GdLQGFe GdfGTFI Yf GSJNOGe GdMGSH GdGdjs; (3JLQje GdhdhLs; (3SQbI GdeGd GdeYdheGJjs; (3GdJRhjQ GdeYdheGJjs; (3LQjeI GdJbdjOs; (3Mbhb GdeDdas; (3GdJhbjY GdGdcJQhfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs